Mitogenic activity of mesenchymal stem cells on hematopoietic stem cells via cellular analysis and gene expression - Mohadeseh, Hashem Boroojerdi (2015)
Introduction: During the last three decades, hematopoietic stem cell (HSC) transplantation has become a well-established treatment for many hematologic malignancies and deficiencies. However harvesting peripheral blood mobilized HSC from donors or cord blood are often hampered by inadequacy of cell numbers. This conundrum drives an alternate way to obtain a required HSC numbers for the demanding clinical therapies. It has been recently revealed that the stromal precursor, mesenchymal stem cells (MSC) profoundly regulates the expansion and differentiation of HSC at bone marrow’s niche via producing hematopoietic growth factors and adhesion molecules. Although the intimate interaction between HSC and MSC is not fully elucidated but it has been confirmed that such communication is mandatory for the uninterrupted hematopoiesis. Objective: Thus, this project is aimed to explore the potential role of MSC in supporting the self-renewal; expansion and differentiation of HSC via cellular and genetic analysis. Materials and Methods: The first phase of this project has focused on optimizing the isolation and characterization of HSC from human cord blood. HSC were isolated using CD34+ magnetic beads and the optimal growth conditions were determined. The holistic effect of MSC on HSC’s life cycle was deduced using various functional assays that measure proliferation, cell cycle, viability, and differentiation status of HSC. At second phase, the molecular interaction between HSC and MSC was further decoded by micro array analysis by measuring largely dysregulated genes in HSC upon co-cultured with MSC. Results: Approximately 80% of HSC were isolated from human cord blood. The optimal growth culture a condition was noticed when HSC were cultured in DMEM-F12 basal media with cytokine cocktails. Expansion index of HSC at in vitro culture was significantly increased in the presence of MSC. Further cell cycle analysis of HSC showed that MSC drove HSC into active cell cycle phase where the larger numbers of HSC were committed to S phase of cell cycle. Flow cytometer analysis of viability and apoptosis status of HSC showed that MSC reduce the apoptosis rate of HSC. In addition, the total number of colonies that formed was generally increased in MSC co-culture. The specific gene expression that induced by MSC during HSC expansion was captured using micro array. The result showed that in the presence of MSC, 712 genes were differentially expressed in HSC. Important genes that involve in controlling the number of HSC such as self-renewal related signaling pathway regulator genes cell cycle and apoptosis regulator genes were categorized by online DAVID software. The detailed analysis revealed that MSC dysregulated some genes that profoundly regulate HSC proliferation. Conclusion: The present study support the notion that the human umbilical cord derived MSC as potential feeder cells that could preserve and amplify the number of human cord blood derived-HSC. The cellular mechanisms that govern this expansion of HSC could be resulted from the protective activity exerted by MSC via reducing apoptosis whilst activating cell cycle. This phenomenon also was well reflected at gene expression study where upregulation of HSC associated proliferation genes evidenced. Our results contributes a great deal to understand the signaling pathways that sustains HSC homeostasis,i.e. self-renewal, differentiation and apoptosis, and the modification of such signals has revealed the first possibilities to in vitro HSC expansion and delineated avenues for its future uses in clinical transplantation.